Two-level total disc replacement with Mobi-C(r) over 3-years - Davis,Reginald (2014)
Objective: To evaluate the safety and effectiveness of two-level total disc replacement (TDR) using a Mobi-C(r) Cervical Artificial Disc at the 36 month follow-up. Methods: a Prospective, randomized, controlled, multicenter clinical trial of an artificial cervical disc (Mobi-C(r) Cervical Artificial Disc) was conducted under the Investigational Device Exemptions (IDE) and the U.S. Food & Drug Administration (FDA) regulations. A total of 339 patients with degenerative disc disease were enrolled to receive either two-level treatment with TDR, or a two-level anterior cervical discectomy and fusion (ACDF) as control. The 234 TDR patients and 105 ACDF patients were followed up at regular time points for three years after surgery. Results: At 36 months, both groups demonstrated an improvement in clinical outcome measures and a comparable safety profile. NDI scores, SF-12 PCS scores, patient satisfaction, and overall success indicated greater statistically significant improvement from baseline for the TDR group, in comparison to the ACDF group. The TDR patients experienced lower subsequent surgery rates and a lower rate of adjacent segment degeneration. On average, the TDR patients maintained segmental range of motion through 36 months with no device failure. Conclusion: Results at three-years support TDR as a safe, effective and statistically superior alternative to ACDF for the treatment of degenerative disc disease at two contiguous cervical levels.